Nurses and Fetal Alcohol Spectrum Disorders Prevention. (3rd July 2019) - Hughes, Erica; Baca, Elizabeth; Mahmoud, Khadejah F.; Edwards, Alexandra; Griffith, Kira J.; Matthews, Emily; Puskar, Kathryn R.; Mitchell, Ann M.
Abstract: Women of reproductive age who are drinking alcohol and not using effective contraception are at-risk for an alcohol-exposed pregnancy, which could result in a child with a fetal alcohol spectrum disorder (FASD). Nurses are an important partner in addressing at-risk alcohol use. It is imperative for alcohol education to be incorporated into nursing curricula so that future nurses have the tools to identify at-risk alcohol use. Three universities have worked together to create Fetal Alcohol Spectrum Disorders: A Toolkit. This toolkit was designed for nurses to facilitate the recognition and prevention of FASD and address gaps that exists around alcohol use.